Leydig cell steroidogenesis unexpectedly escapes mitochondrial dysfunction in prematurely aging mice. Issue 8 (21st April 2015) - Shabalina, Irina G.; Landreh, Luise; Edgar, Daniel; Hou, Mi; Gibanova, Natalia; Atanassova, Nina; Petrovic, Natasa; Hultenby, Kjell; Söder, Olle; Nedergaard, Jan; Svechnikov, Konstantin
Abstract : Point mutations and deletions of mitochondrial DNA (mtDNA) accumulate in tissues during aging in animals and humans and are the basis for mitochondrial diseases. Testosterone synthesis occurs in the mitochondria of Leydig cells. Mitochondrial dysfunction (as induced here experimentally in mtDNA mutator mice that carry a proofreading‐deficient form of mtDNA polymerase γ, leading to mitochondrial dysfunction in all cells types so far studied) would therefore be expected to lead to low testosterone levels. Although mtDNA mutator mice showed a dramatic reduction in testicle weight (only 15% remaining) and similar decreases in number of spermatozoa, testosterone levels in mtDNA mutator mice were unexpectedly fully unchanged. Leydig cell did not escape mitochondrial damage (only 20% of complex I and complex IV remaining) and did show high levels of reactive oxygen species (ROS) production (>5‐fold increased), and permeabilized cells demonstrated absence of normal mitochondrial function. Nevertheless, within intact cells, mitochondrial membrane potential remained high, and testosterone production was maintained. This implies development of a compensatory mechanism. A rescuing mechanism involving electrons from the pentose phosphate pathway transferred via a 3‐fold up‐regulated cytochrome b 5 to cytochrome c, allowing for mitochondrial energization, is suggested. Thus, the Leydig cells escape mitochondrial dysfunction via a unique rescue pathway. Such a pathway, bypassing respiratory chain dysfunction, may be of relevance with regard to mitochondrial disease therapy and to managing ageing in general.—Shabalina, I. G., Landreh, L., Edgar, D., Hou, M., Gibanova, N., Atanassova, N., Petrovic, N., Hultenby, K., Söder, O., Nedergaard, J. Svechnikov, K. Leydig cell steroidogenesis unexpectedly escapes mitochondrial dysfunction in prematurely aging mice. FASEB J. 29, 3274‐3286 (2015). www.fasebj.org